Psychological vulnerabilities among asylum seekers in the Republic of Serbia - Vukčević Marković, Maša; Dimoski, Jana; Šapić, Draga; Živanović, Marko (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
War and concomitant sociopolitical turbulence in the Middle East and Africa have led to big migration flows across the Balkan route - a route that remains active. Numerous refugees sought asylum in Serbia, but only several dozen receive international protection each year. The aim of the study was to assess the level of psychological vulnerabilities among asylum seekers who have submitted asylum applications in the Republic of Serbia. Sixty participants completed the Refugee Health Screener (RHS-15), aimed at screening for depression, anxiety and posttraumatic stress disorder (PTSD) symptoms and assessing overall psychological vulnerability. Results showed that 43.3% respondents were assessed as psychologically vulnerable and 41.7% as highly vulnerable. Moreover, 36.7%, 23.3% and 25% of participants experienced significant levels of depression, anxiety and PTSD, respectively. The importance of providing a comprehensive and trauma-informed model of support during the asylum procedure is discussed.